2014
DOI: 10.1111/jep.12187
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances and causes of falls by patients at a Spanish acute care hospital

Abstract: Falls have diverse causes. Determining these circumstances can contribute to promoting a culture of prevention and to reducing the injuries provoked by falls. Notification procedures should be standardized in order to enable comparisons among different environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 17 publications
6
23
1
4
Order By: Relevance
“…Some previous studies reported that falls often occurred in the patients' rooms (1,3,(13)(14)(19)(20). In our study, 79.2% of falls occurred in patients' rooms, and !…”
Section: Discussionsupporting
confidence: 49%
“…Some previous studies reported that falls often occurred in the patients' rooms (1,3,(13)(14)(19)(20). In our study, 79.2% of falls occurred in patients' rooms, and !…”
Section: Discussionsupporting
confidence: 49%
“…Patient locomotion in the hospital setting is a fundamental issue that demands several care from the nursing staff, including orientation and supervision in an attempt to ensure their safety avoiding the fall. Studies have shown that the majority of falls in hospitalized patients occur from the same height, during walking, on the way to and from the bathroom (4,28,37) . These data reinforce the importance of guiding the patient about the care needed for safe walking.…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to impaired mobility, such as changes in gait and balance, have been identified as predictors of falls, especially in the elderly (2) . A study carried out in a hospital from Spain found that 55.6% of patients who fell required some kind of assistance to move around (another person, a walker or a walking stick) (28) . These data reinforce the importance of patient assessment in relation to their ability to walk and need to use an assistive device, orientation on care and correct use, besides periodic supervision for safety assessment (33) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations